Extraction Optimization and Functional Properties of Protein from Amygdalus pedunculatus Seeds - Zang, X.M.; Chen, B.; Li, C.; Deng, J.J.; Wang, Z.Y.; Shen, Y.H. (Asian Journal of Chemistry, 2013)
Amygdalus pedunculatus seeds contain good-quality proteins. In this paper, maximum yield (55.85 %) was obtained when temperature, extraction time and liquid/solid ratio were 39.49 ºC, 80 min and 15.88:1 (v/w) by using response surface methodology. The amino acid composition of Amygdalus pedunculatus seed protein was analyzed and the proportion of the essential amino acids was closer to the FAO recommended values, among which, glutamic acid was in a particular high level (25.24 % of total amino acid content). The maximum and minimum protein solubility of Amygdalus pedunculatus seed protein were found at pH 10 and pH 4. Water and oil absorption capacity were 2.20 mL H2O/g protein and 2.70 mL oil/g protein. Foaming capacity and emulsifying activity of Amygdalus pedunculatus seed protein were affected by pH (2-10). The least gelation concentration and surface hydrophobicity (S0) were 12 % and 290, respectively. These results indicated that Amygdalus pedunculatus seed protein as a potential ingredient could be used in the food industry.